The Effect of E-Marketing with the AISAS Model on Shariah Mutual Fund Investment Decisions at Bibit Mutual Fund Fintech - Iin Mega Nurjanah; Iqbal Fadli Muhammad; Muhammad Doddy AB (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2020)
This study aims to examine the effect of E-marketing with the AISAS model on mutual fund investment decisions. This research using quantitative research. Data was obtained by distributing online questionnaires to 34 respondents who had or were investing in Bibit Mutual Fund Fintechs that had been registered in the OJK. The sampling technique in this study is purposive sampling, while the Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach is using a data analysis technique. Based on the results of data analysis, Attention variable has a significant effect on Interest variable, Interest variable has a significant effect on Search variable, Search variable has a significant effect on Action variable, Action variable has a significant effect on Share variable, and Share variable has a significant effect on Investment Decisions.